2011
DOI: 10.1111/j.1468-3083.2011.03979.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics of extradigital and digital glomus tumours: a retrospective comparative study

Abstract: Extradigital glomus tumours do not have specific clinical features such as pain, leading to frequent misdiagnosis. To prevent delay in diagnosis or misdiagnosis, it is important to increase awareness of these tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 12 publications
6
103
0
12
Order By: Relevance
“…Unlike digital glomus tumors, which often present with a triad of pain, tenderness to palpation, and cold intolerance, extradigital glomus tumors have a more variable clinical presentation and rarely present with cold hypersensitivity [15]. These benign tumors have a male-to-female predominance greater than 4 to 1 and can present at any time during adulthood [7,15]. Skin discoloration, as seen in our patient, is a common finding [7,15].…”
Section: Discussion and Treatmentmentioning
confidence: 83%
“…Unlike digital glomus tumors, which often present with a triad of pain, tenderness to palpation, and cold intolerance, extradigital glomus tumors have a more variable clinical presentation and rarely present with cold hypersensitivity [15]. These benign tumors have a male-to-female predominance greater than 4 to 1 and can present at any time during adulthood [7,15]. Skin discoloration, as seen in our patient, is a common finding [7,15].…”
Section: Discussion and Treatmentmentioning
confidence: 83%
“…A review of the literature suggests that the extra digital distribution along the upper extremity may be more frequent. The forearm has been noted to be the most common extra digital location, while the shoulder and upper back are the least frequent [2,3]. The classic triad of symptoms described for glomus tumors consists of pain, localized tenderness, and cold hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Extra digital tumors were successfully treated with simple excision without recurrence in 89.5% [17] .…”
Section: Case Presentationmentioning
confidence: 99%
“…Indeed, there was no sensory alteration in the current case in which the glomus tumor was located intravascularly. A retrospective comparative study [17] of the clinical and pathological characteristics of extra digital and digital glomus tumors revealed that patients with extra digital tumors were significantly older (P = .009), with significantly greater male predominance (P < .001). Our index case is 38 years old male.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation